2013
DOI: 10.1371/journal.pone.0064607
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Locus Variable-Number Tandem-Repeat Analysis of Mycoplasma pneumoniae Clinical Specimens and Proposal for Amendment of MLVA Nomenclature

Abstract: Mycoplasma pneumoniae is one of the major respiratory bacterial pathogens that cause pneumonia in humans. Multiple-locus variable-number tandem-repeat analysis (MLVA) is currently the most discriminative method for typing M. pneumoniae strains. To better understand the epidemic of M. pneumoniae-related pneumonia in pediatric patients in Beijing, China, we performed MLVA analysis on 118 specimens collected during an epidemic from 2010–2012. Eleven distinct MLVA types were identified, including four novel types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
80
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(103 citation statements)
references
References 25 publications
17
80
2
Order By: Relevance
“…The detection of extensive intrastrain copy number variation in Mpn1 (Supplementary Table 3) supports the instability of Mpn1 as reported previously [25,33], whereas the absence or presence of low-level intrastrain variation in other four loci in the current MVLA scheme suggests a relatively high stability of these loci. Of note, despite the absence of report of instability of Mpn13 and Mpn14, we detected two or more repeat copy numbers in both loci in a few isolates (Table 2).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The detection of extensive intrastrain copy number variation in Mpn1 (Supplementary Table 3) supports the instability of Mpn1 as reported previously [25,33], whereas the absence or presence of low-level intrastrain variation in other four loci in the current MVLA scheme suggests a relatively high stability of these loci. Of note, despite the absence of report of instability of Mpn13 and Mpn14, we detected two or more repeat copy numbers in both loci in a few isolates (Table 2).…”
Section: Discussionsupporting
confidence: 88%
“…Following the first report of its use in M. pneumoniae in 2009 [15], many studies over the world have consistently shown that MLVA typing is clearly more powerful than the standard P1 typing system in differentiating clinical strains [25,[32][33][46][47][48], and meanwhile there have been rising concerns about its stability, discriminability and correlation to clinical and epidemiological parameters [25,[31][32][33]. These concerns motivated us to seek deeper understanding of We have demonstrated that intrastrain variation occurred in different degrees in all 13 VNTR loci surveyed except for 3 loci (Mpn15, Mpn16 and Mpn103) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLVA types were reported using four loci (Mpn13, Mpn14, Mpn15, and Mpn16) as previously suggested (20)(21)(22). High-resolution melt (HRM) analysis for identification of the macrolide susceptibility genetic profile was performed with a slight modification of the original procedure (9); the modification consisted of using a nested PCR approach to allow standardization of input material into the HRM reactions.…”
Section: Methodsmentioning
confidence: 99%
“…However, the rapid evolution of VNTRs and the recently reported lack of stability of the marker Mpn1 (16), the most discriminant VNTR of the five VNTRs used in this method, are limitations of this technique. Recently, an amendment of the MLVA-5 nomenclature system, which eliminates the unstable Mpn1 marker and bases the typing method on the remaining 4 VNTRs (named the MLVA-4 typing method here), has been proposed (17). With MLVA-4, M. pneumoniae strains were separated into 25 types.…”
mentioning
confidence: 99%